Periodontal disease, but not edentulism, is independently associated with increased plasma fibrinogen levels - Schwahn, Christian; Völzke, Henry; Robinson, Daniel M.; Luedemann, Jan; Bernhardt, Olaf; Gesch, Dietmar; John, Ulrich; Kocher, Thomas (Thrombosis and Haemostasis, 2004)
The systemic response to periodontal disease was analyzed in the cross-sectional Study of Health in Pomerania (SHIP). The completed data of 2,738 subjects aged 20 to 59 years were used for logistic regression analysis with an increased plasma fibrinogen level (≥3.25 g/L according to Clauss) as the dependent variable. Participants were divided into four groups according to the number of periodontal pockets ≥ 4mm (0, 1-7, 8-14, ≥15 pocketing). An additional group comprised the 52 edentulous subjects. The adjusted odds ratio (OR) of ≥15 periodontal pockets for increased plasma fibrinogen levels was 1.88 (95% CI: 1.25-2.83). Edentulism per se was not associated with increased plasma fibrinogen levels but was contained in a two-way interaction with the number of cigarettes/day in current smokers (p = 0.031). For edentulous nonsmokers the adjusted OR was 1.10 (95% CI: 0.51-2.39). Furthermore, body mass index, the interaction between gender and body mass index, serum LDL cholesterol, medication, the interaction between LDL cholesterol and medication, aspirin, smoking, school education, chronic bronchitis, and the interaction between alcohol consumption and chronic gastritis were associated with plasma fibrinogen levels. Our results show that periodontal disease but not edentulism per se is associated with an increased plasma fibrinogen level.
Keywords: Fibrinogen; periodontal disease; Study of Health in Pomerania; SHIP